Application of three‐dimensional proximal isovelocity surface area method in tricuspid regurgitation quantification. Issue 7 (27th June 2019) - Wang, Bing‐Yan; Li, Lian; Zhou, Dan; Zhang, Ming
Abstract: Objectives: Recently, three‐dimensional proximal isovelocity surface area (3D PISA) method has already been widely used in tricuspid regurgitation assessment. This study attempts to demonstrate the feasibility and accuracy of 3D PISA quantifying tricuspid regurgitation and explore the clinical value of 3D PISA in quantifying tricuspid regurgitation. Methods: Fifty‐four patients with more than mild tricuspid regurgitation (TR) were enrolled. Effective regurgitant orifice area (EROA) and regurgitant volume (Rvol) were assessed by transthoracic 3D PISA method and three‐dimensional vena contracta area (3D VCA) method. The 3D VCA was used as reference method. We analyzed the correlation and differences of EROA between 3D PISA method and the reference method. Results: Both EROA and Rvol assessed by the 3D PISA had good correlations with the reference method, particularly in the assessment of eccentric jets, with the correlation coefficients of r (EROA) = 0.83, P < 0.001, r (Rvol) = 0.90, P < 0.001, respectively. 3D PISA method had good agreement with 3D VCA method in grading TR. Intra‐observer and inter‐observer agreement were also good. Conclusions: Three‐dimensional proximal isovelocity surface area method can accurately quantify the degree of tricuspid regurgitation with good repeatability and shorter time‐consuming, which is worthy of further study. 3D PISA method is expected to be a new method for evaluating tricuspid regurgitation in clinic practice.